2016
DOI: 10.1037/bne0000151
|View full text |Cite
|
Sign up to set email alerts
|

The organization of defensive behavior elicited by optogenetic excitation of rat lateral or ventrolateral periaqueductal gray.

Abstract: Rodents display characteristic defense responses to predators that are influenced by predatory imminence. The midbrain periaqueductal gray (PAG) serves an important role controlling these responses. The most influential model states that variations in defensive topography are due to distinct PAG regions: ventrolateral PAG (VLPAG) controls postencounter defense, such as freezing and immobility, whereas lateral PAG (LPAG) controls circa-strike defense, such as escape and flight. Here we used channel rhodopsin (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
66
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 47 publications
11
66
0
1
Order By: Relevance
“…On the other hand, the ventrolateral PAG has been shown to be involved in organizing immobility and freezing during the post-defense recuperative-like quiescent behavior (Assareh et al, 2016;Bandler and Keay, 1996;Bittencourt et al, 2004;Carrive, 1993). However, in contrast to this idea, recent observations by our lab have suggested that the ventrolateral PAG is also seemingly involved in organizing freezing during a predatory encounter (S. R. Mota-Ortiz and N.S.…”
Section: Pag and Fear And Panic Responsesmentioning
confidence: 70%
See 2 more Smart Citations
“…On the other hand, the ventrolateral PAG has been shown to be involved in organizing immobility and freezing during the post-defense recuperative-like quiescent behavior (Assareh et al, 2016;Bandler and Keay, 1996;Bittencourt et al, 2004;Carrive, 1993). However, in contrast to this idea, recent observations by our lab have suggested that the ventrolateral PAG is also seemingly involved in organizing freezing during a predatory encounter (S. R. Mota-Ortiz and N.S.…”
Section: Pag and Fear And Panic Responsesmentioning
confidence: 70%
“…In other words, "postencounter" reflects the initial detection of the potential threat, whereas "circa-strike" is associated with the direct interaction with the predator (i.e., when the predator attacks). Accordingly, both post-encounter and circa-strike defensive behaviors have been ascribed to the dorsomedial, dorsolateral and lateral columns of the PAG, where electrical, pharmacological and optogenetic stimulation have been shown to produce freezing, escape and flight behavior in the absence of a predatory threat (Assareh et al, 2016;Bandler and Keay, 1996;Bittencourt et al, 2004;Carrive, 1993;Deng et al, 2016). Interestingly, dorsal and lateral PAG stimulation may evoke either freezing or escape and jumps, where low magnitude stimuli produced freezing, and slightly higher intensities evoked circa-strike responses (Assareh et al, 2016;Bittencourt et al, 2004;Vianna et al, 2001).…”
Section: Pag and Fear And Panic Responsesmentioning
confidence: 96%
See 1 more Smart Citation
“…used channel rhodopsin (ChR2) stimulation to probe defensive behaviour controlled by the LPAG; suprathreshold LPAG stimulation evoked escape-flight defence that was replaced by freezing at stimulation offset, hence providing more evidence that the LPAG is involved in mediating defence responses (Assareh et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For example, optogenetic activation of the lateral PAG in the rat induces both freezing, and flight behaviors, with higher irradiance needed to evoke flight as compared to freezing behavior (Assareh et al, 2016). Interestingly, these thresholds were lower in the lateral PAG as compared to the ventrolateral PAG.…”
Section: Discussionmentioning
confidence: 99%